High Prevalence of Inadequate Calcium and Iron Intakes by Mexican Population Groups as Assessed by 24-Hour Recalls. Issue 9 (10th August 2016) - Sánchez-Pimienta, Tania G; López-Olmedo, Nancy; Rodríguez-Ramírez, Sonia; García-Guerra, Armando; Rivera, Juan A; Carriquiry, Alicia L; Villalpando, Salvador
Abstract: Background: A National Health and Nutrition Survey (ENSANUT) conducted in Mexico in 1999 identified a high prevalence of inadequate mineral intakes in the population by using 24-h recall questionnaires. However, the 1999 survey did not adjust for within-person variance. The 2012 ENSANUT implemented a more up-to-date 24-h recall methodology to estimate usual intake distributions and prevalence of inadequate intakes. Objective: We examined the distribution of usual intakes and prevalences of inadequate intakes of calcium, iron, magnesium, and zinc in the Mexican population in groups defined according to sex, rural or urban area, geographic region of residence, and socioeconomic status (SES). Methods: We used dietary intake data obtained through the 24-h recall automated multiple-pass method for 10, 886 subjects as part of ENSANUT 2012. A second measurement on a nonconsecutive day was obtained for 9% of the sample. Distributions of usual intakes of the 4 minerals were obtained by using the Iowa State University method, and the prevalence of inadequacy was estimated by using the Institute of Medicine's Estimated Average Requirement cutoff. Results: Calcium inadequacy was 25.6% in children aged 1–4 y and 54.5–88.1% in subjects >5 y old. More than 45% of subjects >5 y old had an inadequate intake of iron. Less than 5% of children aged <12 y and 25–35% of subjects aged >12 y had inadequate intakes of magnesium, whereas zinc inadequacy ranged from <10% in children aged <12 y to 21.6% in men aged ≥20 y. Few differences were found between rural and urban areas, regions, and tertiles of SES. Conclusions: Intakes of calcium, iron, magnesium, and zinc are inadequate in the Mexican population, especially among adolescents and adults. These results suggest a public health concern that must be addressed.